PERAN CURAH HUJAN TERHADAP PENURUNAN HOTSPOT KEBAKARAN HUTAN DAN LAHAN DI EMPAT PROVINSI DI INDONESIA PADA TAHUN 2015-2016 The Role of Rainfall Towards Forest and Land Fires Hotspot Reduction in Four Districs in Indonesia on 2015-2016 - Bambang Hero Saharjo; Wela Alfa Velicia (Jurnal Silvikultur Tropika, 2018)
Forest and land fires are not a new phenomenon for some areas in Indonesia, such as Kalimantan andSumatra. Riau, South Sumatra, West Kalimantan and Central Kalimantan are among provinces that havebeen suffered from severe forest and land fires every year. One of the natural factors affecting forest andland fires occurrences in Indonesia is climate. This study analyzes the relationship between hotspots andrainfall in Indonesia on 2015-2016. The results show that a large number of hotspots is found in the dryseason when the rainfall was less, i.e., on July - October 2015 and July - August 2016. Statistically, monthlyrainfall and monthly hotspots has a negative correlation (-) with R2 = 42.5% and P-value = 0.001. Theequation built is y = 3182 - 2.50x, where y denotes hotspots and x for rainfall.Key words: forest and land fires, hotspot, rainfall